THE ROLE OF THE NEIGHBORHOOD IN PROVIDING THE EMPLOYMENT OF THE POPULATION AND THE POSSIBILITIES OF USING THE "AID FUND" MODEL IN IT (World Economics and Finance Bulletin, 2023)
In the article, special importance is given to the location of the neighborhood in ensuring the employment of the population. In this regard, indicators of self-employment of the population in foreign countries, some of their limitations and facilities were considered, and conclusions and proposals were developed through the analysis of the occupations and population coverage that can be self-employed in the conditions of Uzbekistan
Keywords: Employment; self-employment; neighborhood